Problems perceived and experienced by health professionals rendering social service in Ancash, Peru. 2015 - Taype-Rondan, Álvaro (2017)
Introduction: Social health services in Peru have certain problems such as unsafe work conditions, mortality associated with traffic accidents and poor insurance coverage. Objective: To describe the problems perceived and experienced by health professionals who render Rural and Urban Marginal Health Service (SERUMS in Spanish) in Ancash (Peru), and to evaluate their association with the profession and the category of the facilities where SERUMS is rendered. Materials and methods: In April 2015, an analytical cross-sectional study was carried out in professionals who were rendering SERUMS in facilities of the Ministry of Health in Ancash. Surveys were applied to collect general data, and characteristics and problems of SERUMS. Results: 364 surveys were analyzed. 79.3% were females, and the average age was 27.4±5.0 years. During SERUMS, 80.0% of participants perceived lack of supplies, 54.4% perceived excessive workload, and 14.7% suffered some traffic accident. Being a physician and working in I-1 health facilities were factors associated with suffering traffic accidents and other kind of accidents. Conclusions: Respondents reported excessive workload, lack of supplies, and accidents. Accidents were more frequent in physicians and in I-1 health facilities.